ON RATINGS AND RANKS - Andrey V. Belotserkovsky (Высшее образование в России)
Ranking of HEI is considered. International experience, scientific background for choosing indicators are taken into account. Some views on opportunities and risks of making decisions based on the popular international universities ranking are expressed.